Disseminated Mycobacterium chimaera Following Open-Heart Surgery, the Heater–Cooler Unit Worldwide Outbreak: Case Report and Minireview - Lecorche, Emmanuel; Pean de Ponfilly, Gauthier; Mougari, Faiza; Benmansour, Hanaa; Poisnel, Elodie; Janvier, Frederic; Cambau, Emmanuelle (Frontiers in Medicine, 2020)
Invasive cardiovascular infections by Mycobacterium chimaera associated with open-heart surgery have been reported worldwide since 2013. Here, we report a case of a 61 year old man, without any other particular medical background, who underwent cardiac surgery for replacing part of the ascending aorta by a bio-prosthetic graft. Eighteen months later, the patient was painful at the lower back with fever. A pyogenic vertebral osteomyelitis due to M. chimaera associated to graft infection was diagnosed after 6 months of sub-acute infection. The patient presented a disseminated disease with cerebral lesions, chorioretinitis, and chronic renal failure. Despite adequate antimicrobial treatment and graft explantation, the patient died after 6 years. We reviewed the literature on M. chimaera infections associated with open-heart surgery. The worldwide outbreak has been explained by airborne bioaerosol generated by the 3T heater–cooler unit (HCU) used during cardiac by-pass surgical procedures. These infections are difficult to diagnose because of a long latency period (up to several years), with no specific symptoms and a highly specialized microbiological diagnosis. The treatment is based on antibiotics and surgery. These infections are also difficult to treat, since the mortality rate is high around 50%. Prevention is necessary by modifying the use of HCUs in operating rooms.